TRENDS IN CHANGES OF SETTLEMENT PATTERN IN THE BORDER ZONE OF THE REPUBLIC OF ARMENIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2026)
Trends in changes of settlement patterns and population dynamics in the border zone of the Republic of Armenia (RA) are shaped by border security and socio-economic issues. The border zone accounts for 24.0% of the territory of the RA. This zone contains 21.3% of all settlements and accommodates 7.7% of the country's population. The article examines the specific features of settlement patterns in the RA border zone, recent transformation trends over the past five years, and state programs aimed at the development and support of border settlements. A map of the RA border settlements has been compiled.
Keywords: border zone; resettlement; border; border settlement